Floristic Composition and Stand Structure of The Mountain Forest Post-Fire in Mount Ciremai National Park, West Java - Hilwan, Iwan; Laijanan, Theresia Avilla (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Forest fires occurred in Mount Ciremai National Park (TNGC) area during the period from 2011 to 2022. These fires led to secondary succession, altering the composition and structure of the forest stands. This research aims to analyze the floristic composition and vegetation structure of the mountain forest post-fire. Data collection was conducted through vegetation analysis in two land cover types: primary forest and post-fire 2019 forest. The research shows a difference in the number of tree species found in the post-fire forest, and the number of plant species were recorded in sampling plots are totally 90 species of the 43 families. The ground cover plant was dominated by the species Orthosiphon aristatus, while the seedling and sapling stages were dominated by Cinchona calisaya, the pole stage was dominated by Oreocnide rubescens, and the tree stage was dominated by Macaranga tanarius. The plant diversity of the primary forest was relatively higher and the composition of tree stage in the primary forest and the post-fire 2019 forest were close to similar. The horizontal structure of the forest stands showed an inverted J-shaped curve, while the understory trees dominated the vertical structure. Keywords: fire, floristic composition, mountain forest, Mount Ciremai National Park, stand structure